극박막의 결정성 및 전기적 특성 확보를 위한 HfO2 내 희토류 도핑 연구 - 오근하 (The Graduate School, Ajou University, 2024)
Efforts to enhance crystallization temperature and reduce leakage currents in HfO2 thin films led to the study of doped HfO2 films using supercycle atomic layer deposition (ALD). However, conventional doping methods, especially in ultrathin films below 5 nm, face challenges in controlling mixing ratios. In this study, we employed atomic layer modulation (ALM), a novel ALD doping method, to create Dy-doped HfO2 films. ALM facilitates multicomponent film growth, even at the monolayer level, by sequentially exposing two precursors followed by oxidation through a single reactant exposure. Consequently, the ALM process allows for more precise control over the thickness of doped films compared to the supercycle method, facilitating the fabrication of ultrathin Dy-doped HfO2 films. Our findings indicate that Dy dopants in 5 nm thick Dy-doped HfO2 films deposited at 250 °C by ALM inhibit the crystallization of HfO2 at 600 °C. Additionally, we investigated the difference in Dy doping concentration in ALM films where the Hf precursor was exposed firstly compared to those where the Dy precursor was initially exposed (Dy doping concentration was 12.5% and 20.6%, respectively). Moreover, the ALM film with the Hf precursor exposed first exhibited a leakage current value approximately 180 times lower than its counterpart. Our results highlight the potential of ALM in fabricating ultrathin doped oxide films efficiently, providing new insights and perspectives in the semiconductor material process as semiconductor oxide thickness scales down to 5 nm and below.
학위논문(석사)--지능형반도체공학과,2024. 2
Keywords: Atomic layer deposition; Dy-doped HfO2; atomic layer modulation